Potential and Challenges of Organic Rice Development in Pringsewu Regency, Lampung : A Review of Secondary Data to Support Local Food Security (International Forum of Researchers and Lecturers, 2025)
The development of organic rice agribusiness is a strategic effort to achieve sustainable food security in Pringsewu Regency, Lampung Province. This study aims to analyze the production potential, institutional support, existing challenges, and market opportunities for organic rice development. The research highlights that rice productivity in Pringsewu is relatively high, averaging 5.68 tons per hectare, indicating favorable agroecological conditions. However, the certified organic farming area remains very limited, covering less than 15 hectares, which constrains the scale of production and the ability to meet growing market demand. Institutional aspects reveal that farmer groups and agricultural extension agents have demonstrated active participation in promoting organic farming practices. Nevertheless, institutional integration, coordination among stakeholders, and the establishment of sustainable value chains remain suboptimal. This lack of synergy often slows the certification process and limits collective marketing strategies. From a market perspective, organic rice presents promising prospects, with an annual demand growth rate estimated at 15–20%. The premium price of organic rice compared to conventional varieties provides significant income incentives for farmers. Despite this, several challenges must be addressed, including the complexity and cost of organic certification, limited supply continuity, and inadequate post-harvest infrastructure. Without targeted interventions, these barriers may hinder the expansion of organic rice agribusiness in the region. The study concludes that the success of organic rice agribusiness development in Pringsewu will largely depend on strengthening farmer institutions, enhancing policy coordination between local government and related agencies, and improving access to domestic and export markets. Strategic investments in certification facilitation, infrastructure development, and farmer capacity building are essential to accelerate the transition toward sustainable agricultural practices and to secure the region’s contribution to long-term food security.